Exploration des activités antioxydantes et antimicrobiennes de quelques huiles essentielles comme conservateurs naturels. - Bakhtia, Mohamed Rafik; Berdji, Imene (My University, 2022)
The present study aims to evaluate the antioxidant and antimicrobial activities of some essential oils from clementine and lemon peels, as well as spearmint, verbena and fennel leaves for possible use as natural food preservatives. The extraction of essential oils was carried out by steam distillation. The evaluation of antioxidant activity was carried out with the DPPH test, the antimicrobial activity by the disk diffusion method and the minimum inhibitory concentrations by the microdilution method. All essential oils had a good antioxidant activity with free radical DPPH inhibitions ranging from 66.05% to 93.82% at only 0.02 mg/mL concentration. The IC50 concentrations were ranged from 0.0114 to 0.0117 mg/mL, the best results were recorded with mint and clementine. In which concern the antimicrobial potency, all essential oils had good activity against all tested strains recording inhibition zones ranging from 11.75 to 21 mm, and a minimum inhibitory concentration of 0.0781 to 0.625 mg/mL. Essential oils from clementine peels, followed by mint leaves, then lemon peels had the highest antimicrobial activity.
Keywords: Essential oil; antioxidant activity; antimicrobial activity; natural preservative